Tourism as a Driver of Local Economic Development: A Case Study of Micro Business Actors in the Nirwana Beach Area, Bau-Bau. - Alfin Siolombona; Abdul Salam (Jurnal Manajemen dan Inovasi Pariwisata, 2026)
Tourism is a strategic sector with great potential to drive local economic growth, particularly through the involvement of micro business actors as a key component of the tourism ecosystem. This study aims to examine the role of tourism as a driver of the local economy from the perspective of micro business actors, identify the structural challenges they face, and describe the adaptation strategies applied in responding to the dynamics of the tourism sector. This study uses a qualitative approach with a descriptive-exploratory research design. Data were collected through in-depth interviews, participant observation, and documentation studies of micro business actors operating in tourist areas, including culinary businesses, handicrafts, transportation services, simple lodging, and other tourism support services. Data analysis used the interactive analysis model of Miles, Huberman, and Saldaña (2023), with data validity ensured through source and method triangulation. The results show that tourism plays a real role in increasing income, creating local jobs, and driving the diversification of micro business products. However, micro business actors still face four main challenges: limited access to capital, income fluctuations due to dependence on the tourist season, limited managerial and digital capacity, and competitive pressure from business actors outside the region. In response, micro business actors apply strategies of strengthening local product identity, business network collaboration, and the adoption of digital marketing. This study concludes that the inclusion of micro businesses in the tourism value chain is a fundamental prerequisite for achieving just and sustainable tourism development, requiring affirmative policies that are more systematically and structurally oriented toward local micro business actors.